(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم التخدير و الإنعاش بالتعاون مع قسم الجراحة العامة خلال العام 2005 – 2006 وتضمنت 60 مريضاً خضع كل واحد منهم لعملية شرجية جراحية تحت التخدير الذيلي. و كانت نتائج الدراسة على النحو الآتي: • لم تحدث تغيرات قلبية وعائية ذات أهمية. • حدث الفشل في إيجاد الفرضة العجزية بنسبة 10 %. • حدث الأسر البولي بنسبة 15 %. • لم يحدث الحقن داخل الوريد أو العظم أو بزل الجافية. • حدث ألم أثناء الحقن عند 20 %. • كانت فترة الكمون: ( 10 ) دقائق بالنسبة لليدوكائين و بالنسبة للمزيج ( ليدوكائين + بوبيفاكائين ). ( 15 ) دقيقة بالنسبة للبوبيفاكائين. • كانت مدة الحصار: ( 90 ) دقيقة بالنسبة لليدوكائين. ( 120 ) دقيقة بالنسبة للبوبيفاكائين وبالنسبة للمزيج ( ليدوكائين + بوبيفاكائين ). This study was carried out in the Department of Anesthesia and Reanimation in collaboration with the Department of General Surgery at AL-ASSAD University Hospital, Lattakia, during the year 2005-2006. It included 60 patients who underwent to anal surgery under caudal anesthesia. The results were as follows: • There were no significant cardiovascular changes. • We could not find sacral hiatus in 10%. • Urinary retention occurred in 15%. • There was no intravenous or intraosseous injection or durapuncture. • There were pain during injection in 20%. • Latent period was: (10 ) minutes for lidocaine and for the mixture (lidocaine + bupivacaine ). (15 ) minutes for bupivacaine. • Time of block was: (90) minutes for lidocaine. (120) minutes for bupivacaine and for the mixture (lidocaine + bupivacaine ).